Strategies for Strengthening Religious Values Through the Tahfidz Al-Qur’an Program in Responding to the Challenges of Modernization - Intan Astina Dewi; Danny Abrianto (Al-Fikru: Jurnal Ilmiah, 2025)
he moral crisis of the younger generation characterized by a decline in discipline, responsibility, and social care is a serious challenge for Islamic educational institutions to restore the role of education as a character builder. This study aims to describe the strategy of strengthening religious values through tahfidz Al-Qur'an activities at the Ar-Roja Bina Insani Foundation in Kisaran, North Sumatra. The research uses a descriptive qualitative approach with phenomenological methods, through interviews, observations, and documentation of foundation leaders, tahfidz ustaz, students, and parents. The results showed five main strategies implemented: integration of memorization and understanding of verses, exemplary teachers in behavior, habituation of daily worship, active involvement of parents, and creation of a conducive religious environment. These strategies proved effective in fostering discipline, patience, honesty, and responsibility of the students. This research confirms that the Qur'an tahfidz program is not just an effort to memorize, but a comprehensive Islamic character building medium. The implication is that the tahfidz program can be used as a model of religious character education that is adaptive and relevant in answering the moral challenges of modern society.